Egg and Dietary Cholesterol Consumption and Mortality Among Hypertensive Patients: Results From a Population-Based Nationwide Study - Wu, Fei; Zhuang, Pan; Zhang, Yiju; Zhan, Chuchu; Zhang, Yu; Jiao, Jingjing (Frontiers in Nutrition, 2021)
Background: Hypertensive patients are sensitive to the amount of dietary cholesterol intake, especially cholesterol from whole eggs. Whether whole egg and dietary cholesterol consumption is suitable for hypertensive patients is still controversial. Aim: The objective of the study was to examine the associations of intakes of eggs as well as dietary cholesterol with total mortality in a Chinese nationwide cohort. Methods: We utilized data from the China Health and Nutrition Survey (CHNS) from the year of 1991 to 2015. Cumulative averages of egg and cholesterol intakes were calculated to represent long-term diets consumption of participants in each available round of survey. Cox regression models were employed to estimated effects of eggs and dietary cholesterol from different sources on mortality among hypertensive patients. Results: 8095 participants were included in the final analysis and followed up for a mean of 11.4 years. Finally, 927 cases of death were detected. After adjusted for multivariate factors, consuming more than 7 eggs per week was related to 29% lower mortality among hypertensive patients compared to consumers with not more than 2 eggs per week [hazard ratio (HR): 0.71; 95% confidence interval (95% CI): 0.59-0.85; P-trend<0.001]. Similarly, egg-sourced cholesterol intake was inversely associated with mortality (P-trend=0.002) whereas intake of dietary cholesterol from non-egg sources was significantly related to higher mortality (P-trend<0.001). However, total cholesterol intake was not related to mortality among hypertensive patients. Substituting eggs for equivalent amount of non-egg-sourced protein-abundant foods was also associated with lower mortality. Conclusion: Higher consumption of egg and egg-sourced dietary cholesterol was associated with lower mortality among enrolled Chinese hypertensive patients but non-egg-sourced cholesterol intake was related to higher mortality. Therefore, our findings do not support the view that hypertensive patients should avoid whole egg consumption for the purpose of restricting dietary cholesterol intake.